ANALISIS PENERAPAN MANAJEMEN RISIKO DALAM PENGELOLAAN BISNIS ANGKUTAN UMUM RODA TIGA (STUDI KASUS PADA POOL BAJAJ SUNTER, JAKARTA UTARA) - Muhamad Ihsan; Ismaya, Betty (P3M Trisakti School of Insurance (TSI), 2022)
This research to understand the application of risk management to Bajaj’s business and operational, including to its business sustainability, with the object of this research is the Bajaj Pool Sunter-North Jakarta. The main source of risk exposure exploration are interviews through 3 (three) sources, namely the Owner, Manager, and Driver. The frequency(ies) and impact(s) as parameter to define and classified the risk category. There are 6 (six) risk with significant impact to disrupted the Bajaj business sustainability and 3 (three) risk with significant impact to disrupted the operational of Bajaj. The risk treatment currently by own retention or self-insured because not yet availability the insurance product against that risk.